(untitled) (Philological Studies, 2019)
In this paper we shall consider several aspects in which we can investigate the occurrence, the presence, and the significance of wine in the Balkans. We will use data from ethnolinguistics and folk literature, especially the presence of giving a toast and the cult of drinking wine in epic poetry, as well the etiological legends that analyze the origins of wine. In addition to this, some accompanying ritual and cult actions will be analyzed that may explain the significance and meaning of wine in some parts of traditional folk culture